An assessment of Genetic and Social Aspects of Breeding (Endogamy and Exogamy Marriages) Practices in Homo sapiens - Das, Bishnu Dev; Paudel, Niroj (Darul Yasin Al Sys, 2025)
This study provides an extensive evaluation of the genetic and social aspects of breeding practices, specifically endogamy and exogamy, in Homo sapiens. Endogamy, the custom of being married within the custom of being married within a specific social, ethnic, or religious group, and exogamy, the tradition of being married outside one’s group, have profound implications for both genetic diversity and social structures. Socially, endogamy reinforces cultural identity and group cohesion, preserving traditional practices and hierarchical structures within communities. Conversely, exogamy promotes social integration and the alliances forming between various groups, reflecting modern shifts towards individual choice and inclusivity. Genetically, endogamy can lead to reduced genetic diversity and an increased risk of hereditary disorders due to inbreeding. Populations practicing endogamy may exhibit higher frequencies of genetic diseases as a result of the accumulation of deleterious alleles within a closed gene pool. In contrast, exogamy enhances genetic diversity, which can improve overall population health and adaptability by reducing the risks associated with inbreeding and introducing new genetic variations. However, exogamy may also dilute specific genetic adaptations unique to certain environments. The study highlights how these breeding practices impact genetic health and social dynamics, illustrating the balance between preserving cultural heritage and fostering genetic diversity. The findings underscore the importance of understanding these practices in the context of modern societal changes and technological advancements, which continue to shape human reproduction and social organization. This assessment provides valuable insights into the evolving nature of human breeding practices and their implications for future genetic and social outcomes.